Kesiapan Penerimaan Kepala Sekolah terhadap Teknologi Google Docs: Studi Kasus Pelatihan Calon Kepala Sekolah Dasar Kabupaten Ngaawi - S T Nurjaningsih (Teknodika, 2019)
One of the technology-based applications cloud computing introduced to the participants of primary school principals education training is theapplication Google Docs. Use ofapp technology Google Docs or known Google Docs is causing a reaction on the user himself, namely in the form of acceptance and rejection. The acceptance of a technology is strongly influenced by the readiness of the users of the technology. This study aims to examine whether the participants of the candidate head sekolaj SD Kabupaten Ngawi already have the readiness and acceptapplication technology Google Docs for individual task completion when On The Job Learning in school alone and a second internship. The model used to describe the relationship that factors affect the readiness and usage of theapplication Google Docs is the Technology Readness Index (TRI) on Technology Acceptance Model (TAM) by the method research using factor analysis on SPSS software version 18.0. The result variable self-ability to computer and variable of readiness that is optimistic and innovation have an effect on signifikan to variable of acceptance.